Pelatihan Pembuatan Lilin Aroma Theraphy di Desa Mojoagung Soko Kabupaten Tuban - Nurul Novitasari; Chilyatul Azkiyya; Ayu Puji Lestari; Azimatul Ulya; Devi Mustika Ramadhani; Elfiana Anggita Dewi; Irma Improatul Fitria; Mastura Laelatul Fajar; Miftakhul Jannah; Nur Aini Lu’luatin; Safira Nurulita; Siti Kholisoh; Siti Qudrotun Nada; Tega Silvia Antika; Ulva Romadhotul Fatimah; Rina Khumaimah (Lembaga Pengembangan Kinerja Dosen, 2023)
Candles are a tool that can fulfill human needs. Apart from being a light, candles can also be used as home decoration and are a useful tool in assisting the therapy process and can support a modern healthy lifestyle. In this case, the function of candles increases, such as fragrances, which can light up and spread a fragrant aroma throughout the room. To relax the body and create calm, and help relieve symptoms of stress. Can support a positive mood and can increase energy for the body. Candles are a tool that can fulfill human needs. Apart from being a light, candles can also be used as home decoration and are a useful tool in assisting the therapy process and can support a modern healthy lifestyle. In this case, the function of candles increases, such as fragrances, which can light up and spread a fragrant aroma throughout the room. To relax the body and create calm, and help relieve symptoms of stress. Can support a positive mood and can increase energy for the body.